Exploring How Motivation and Compensation Influence Employee Performance in A Bandung Industrial Company - Ratno Heru Triwibowo; Dedi Hadian; Aan Hardiyana; Djadjat Suswanto; Titi Titi (P3M, Sekolah Tinggi Ilmu Ekonomi Pasundan Bandung, 2025)
This research explores the main issue regarding human resource management at a Bandung Industrial Company, which poses a significant challenge for organizational sustainability in the era of globalization. The primary objective of this study is to identify factors influencing employee performance, with a focus on motivation and compensation. The research methodology employs descriptive analysis based on performance data and employee satisfaction surveys. The findings reveal that employee performance still falls short of company expectations, with both the quantity and quality of work not meeting the desired targets. The novelty of this study emphasizes the critical role of motivation and compensation in enhancing performance, a factor often overlooked. The implications of these findings suggest the need for more effective management strategies in handling motivation and compensation to optimally drive employee performance, enabling the organization to achieve its desired goals.